The Effect of Self-Assessment and Students’ Learning Autonomy towards Students’ Performance in Vocational Education - Ni Ketut Widiartini; Ni Wayan Sukerti (Universitas Pendidikan Ganesha, 2023)
Creating an independent learning process realized through student-centred learning is quite challenging by many vocational educators particularly in selecting appropriate learning method. Therefore this study was purposed to analyze the effect of self-assessment and students’ learning autonomy towards students’ performance in vocational education. Quasi-Experimental with 2x2 factorial design was used as the research model of this study by involving 60 fourth semester students who took fashion design course. They were selected by using random-matching sampling technique. The data were collected thorough pre-test and post-test in which self-assessment and performance test rubrics were used as research instruments. The obtained data were analysed quantitatively particularly by conducting descriptive quantitative and inferential statistical analysis with the assistance of SPSS.25. The results showed that self-assessment along with the students’ learning autonomy affected students’ performance. Self-assessment improved students’ performance in which it was inseparable from learning autonomy as the influencing factor. In addition, the results drew that students were directly involved in the learning process and self-assessment was maximized by students’ learning autonomy in affecting their performance. The implication of this study strengthens the use of self-assessment and learning autonomy towards students’ performance in fashion design course.